CYBERLEARNING AND TEACHER QUALITY: A HOLISTIC APPROACH TO ENHANCING EDUCATION IN INDONESIA, TEACHER READINESS FOR CYBERLEARNING - Mas'ud Muhammadiah; Merliana Trince; Andi Hamsiah; Adi Asmara; Mohammad Ahmad Bani Amer (International Journal of Teaching and Learning, 2023)
Recently, Indonesia has witnessed a remarkable transformation in its educational landscape, driven by the increasing integration of technology into teaching and learning processes. This shift towards cyberlearning has been a pivotal catalyst in reshaping education dynamics within the nation. This paper delves into an extensive research endeavor that explores the profound relationship between cyberlearning and teacher quality and its subsequent impact on the overall quality of education in Indonesia. Our study, set in the past, delves into a comprehensive examination of teachers' readiness for the digital era. It explores how educators have navigated the transition towards cyberlearning and the challenges and opportunities this transformation presents. We delve into the past landscape of teacher preparation and their ability to harness the potential of technology in their classrooms. As we voyage into the past, we aim to unearth critical insights into the evolution of teacher readiness for cyberlearning and how it has influenced the educational fabric of Indonesia. The past becomes a portal through which we dissect the foundations of this transformation, providing valuable lessons and insights for the future of education in Indonesia.